Bridging Traditional Knowledge and Modern Technology: Artificial Intelligence in Anatomy Education for Ayurveda - Bharat Pathak,; Devi Tiwari,; Dipesh Tiwari, (Journal of Ayurveda Campus, 2025)
Background: Ayurveda education has always placed a strong emphasis on anatomy (Sharira Rachana), which serves as the basis for both clinical practice and surgical proficiency.  Although traditional mentorship and cadaver dissection are still the gold standards, contemporary issues such as scarce cadavers, resource limitations, and the cognitive dissonance between classical and biomedical anatomy necessitate creative pedagogical approaches.  Tools powered by artificial intelligence (AI), like augmented reality (AR), virtual reality (VR), and adaptive learning platforms, present exciting opportunities to improve anatomy instruction.Methods: This conceptual review combines ideas from contemporary literature on medical education and digital learning technologies with insights from traditional Ayurvedic texts (Charak Saṃhitā, Suśruta Saṃhitā, and Aṣṭāṅga Hṛdaya).  Search terms such as "AI in anatomy education," "AI and Ayurveda," "Virtual Anatomy," "Digital Anatomy Models," and "Traditional Medicine Education" were used to search electronic databases (PubMed, Scopus, Google Scholar, DOAJ, and ScienceDirect).  In order to identify connections between traditional Ayurvedic anatomical knowledge and AI-enabled pedagogical strategies, pertinent findings were critically examined.Results and Discussion:Although lectures and cadaver-based training are important components of traditional Ayurvedic education, widespread access is constrained by ethical, practical, and financial issues.Recent developments show how VR/AR simulations, virtual dissections, and intelligent tutoring systems can improve engagement, customize learning, and harmonize Ayurveda's epistemology with modern anatomy models. Examples of these developments include CADAVIZ, AyurSIM, and AI-powered adaptive platforms.AI has the ability to make anatomy education more approachable and culturally aware in Nepal, where cadaver shortages and resource disparities are still severe, while maintaining dissection and mentorship as essential pillars. Conclusion: AI-powered tools offer a revolutionary chance to integrate contemporary technological methods in anatomy education with traditional Ayurvedic knowledge.  When used carefully, they can enhance rather than replace established techniques, increasing the interactivity, personalization, and clinical relevance of anatomy education.  Combining AI with Sharira Rachana pedagogy in Ayurvedic programs in Nepal and elsewhere could result in graduates who are more equipped to handle regional and international healthcare issues.